Triphenylamine triazine compound as well as preparation and application thereof in explosive and drug detection

Through the C-O coupling reaction preparation method of D-A type polytriphenylamine triazine compounds, the problems of complicated preparation, low quantum yield and insufficient detection sensitivity of existing triphenylamine polymers in drug and TNT detection are solved, and high response is achieved The detection effect of drugs and TNT is stable and low detection limit.

CN119330899AActive Publication Date: 2025-01-21SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411379197.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In drug detection and TNT detection in water, existing tripaniline polymers have problems such as complex preparation steps, low quantum yield, insufficient detection sensitivity and high detection limits.

Method used

D-A type polytriphenylamine triazine compound is prepared through a one-step C-O coupling reaction, using 4,4'-difluorodiphenyl sulfone and triphenylamine-triazine structure compounds as reaction monomers, and potassium carbonate as an alkaline catalyst .

Benefits of technology

It achieves high responsiveness of the drug albuterol sulfate solution and low detection limit of TNT in water (39nM-70nM). It also has good anti-interference ability and is almost unaffected by pH, other nitro compounds, metal cations and anions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330899A_ABST
    Figure CN119330899A_ABST
Patent Text Reader

Abstract

The invention provides a compound with a triphenylamine-triazine structure, a D-A type polytriphenylamine-triazine compound, preparation methods of the compound and the D-A type polytriphenylamine-triazine compound and application of the compound to drug detection and TNT content detection in a water body, and belongs to the technical field of drug quality detection and environment detection in the water body. The structural formula of the compound with the triphenylamine-triazine structure provided by the invention is as shown in the formula lt, igt; the structural formula of the D-A type polytriphenylamine triazine compound is as shown in the formula lt, iI < gt >; x is-SO2 <-> or-CO <->. The D-A type polytriphenylamine triazine compound has strong luminescence performance, can be well used for detection of drugs such as a salbutamol sulfate solution, and can also be used for detection of trace TNT. The extremely low detection limits on TNT (trinitrotoluene) are respectively 39 nM and 70 nM. Meanwhile, the fluorescent probe shows good anti-interference capability, and is almost not influenced by potential factors such as pH, other nitro compounds, metal cations and anions and the like. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of drug detection and environmental detection in water bodies, and specifically relates to a triphenylamine-triazine structure compound and a DA type polytriphenylamine triazine compound and a preparation method thereof and application thereof in drug detection and explosive detection. Background Art

[0002] Drug dosage control is the key to ensuring drug efficacy, so the detection of drug dosage or impurities has become a key process to ensure drug quality. For drugs such as salbutamol sulfate solution, the use of fluorescence detection methods is expected to control quality.

[0003] On the other hand, 2,4,6-trinitrotoluene (TNT) is a high explosive widely used in military and industrial fields. However, TNT is biologically toxic, difficult to degrade, and can cause irreversible destructive effects on the environment, so it is particularly important to monitor TNT in the environment.

[0004] In recent years, in the face of drug quality control and the detection of nitroaromatic explosives such as TNT in water, various instrument-based analytical techniques have developed rapidly, covering chromatography, mass spectrometry, gas chromatography-mass spectrometry, X-ray imaging, Raman spectroscopy, ion mobility spectrometry, electrochemical analysis and other methods. The emergence of these technologies has greatly promoted the progress of detection technology. However, these devices are often bulky and difficult to carry, making it difficult to meet the needs of real-time and on-site monitoring, especially in outdoor environmental monitoring situations where data needs to be obtained quickly. This limitation not only reduces the efficiency of on-site detection, but also increases the feedback time. In contrast, fluorescence-based detection methods have been used in portable detection equipment as early as the last century due to their simple operation, low cost, high sensitivity and excellent selectivity, and have therefore been widely used.

[0005] As a classic organic semiconductor material, triphenylamine shows great potential in the construction of fluorescent probes due to its unique electron-rich properties, geometric configuration and chemical stability. However, the current triphenylamine-based fluorescent probe materials face many challenges, such as complex synthesis, low yield and difficulty in large-scale production.

[0006] Typically, the synthesis of triphenylamine polymers requires the introduction of reactive functional groups in advance, followed by polymerization reactions. This method inevitably involves more synthesis steps and higher costs. In addition, unmodified triphenylamine polymers exhibit low quantum yields in aqueous media, and usually require modification with aggregation-induced emission (AIE) groups such as tetraphenylethylene to enhance the luminescence efficiency of the aggregated state. This limitation seriously affects the application of triphenylamine polymers as fluorescent probes for TNT in water.

[0007] Therefore, how to provide a preparation method for triphenylamine polymers with a simple preparation method, high yield, good responsiveness to drugs such as salbutamol sulfate solution, low detection limit for TNT in water, good anti-interference ability, and almost no influence by potential factors such as pH, other nitro compounds, metal cations and anions, has become a technical problem to be solved urgently. Summary of the invention

[0008] The present invention is to solve the above technical problems, thereby providing a DA type polytriphenylamine triazine compound and its application in drug detection and TNT content detection in water, so as to solve the problems of the existing triphenylamine polymers, such as complicated preparation steps, low quantum yield, insufficient detection sensitivity for salbutamol sulfate solution and TNT, and high detection limit.

[0009] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0010] The present invention first provides a triphenylamine-triazine structure compound, characterized in that the triphenylamine-triazine structure compound has a structural formula as shown in the following formula <Ⅰ>:

[0011]

[0012] The second object of the present invention is to provide a method for preparing the triphenylamine-triazine structure compound as described above, which comprises dropping dimethyl sulfoxide into a mixture containing 4-hydroxybenzamidine hydrochloride, 4-diphenylaminobenzaldehyde and cesium carbonate, heating the mixture for a period of time, precipitating the product and performing multiple extractions to obtain a crude product, and purifying the crude product by column chromatography.

[0013] Furthermore, the molar ratio of 4-hydroxybenzamidine hydrochloride, 4-diphenylaminobenzaldehyde and cesium carbonate is 2-2.5:1-1.2:2-2.5.

[0014] Furthermore, the reaction temperature is 120-140° C., and the reaction time is 16-20 hours.

[0015] The third object of the present invention is to provide a DA type polytriphenylamine triazine compound, the structural formula of the DA type polytriphenylamine triazine compound is shown in the following formula <Ⅱ>:

[0016]

[0017] Wherein, X is -SO2- or -CO-.

[0018] Furthermore, the average lifetime <τ>avg of the DA type polytriphenylamine triazine compound is 3.62 to 3.75 ns, and the fluorescence quantum yield in water is It is 0.39~0.53.

[0019] Furthermore, the thermal decomposition temperature of the DA type polytriphenylamine triazine compound is 538-564°C, and the glass transition temperature is 197-220°C.

[0020] Furthermore, the DA-type polytriphenylamine triazine compound has a fluorescence quenching response to the drug salbutamol sulfate solution, and the detection limits for TNT in water are 39 nM and 70 nM, respectively.

[0021] The fourth object of the present invention is to provide a method for preparing the DA type polytriphenylamine triazine compound as described above, which is prepared by a one-step CO coupling reaction under a nitrogen atmosphere using 4,4'-difluorodiphenyl sulfone and a compound with a triphenylamine-triazine structure as reaction monomers and potassium carbonate; wherein the reaction monomer is prepared from 4-hydroxybenzamidine hydrochloride, 4-diphenylaminobenzaldehyde and cesium carbonate.

[0022] Furthermore, the molar ratio of the 4,4'-difluorodiphenyl sulfone, the compound with triphenylamine-triazine structure and potassium carbonate is 1-1.2:1-1.2:1.5-2.0.

[0023] Furthermore, the reaction temperature of the CO coupling reaction is 150-180° C., and the reaction time is 6-12 hours.

[0024] The fifth object of the present invention is to provide the above-mentioned triphenylamine-triazine structure compound and DA type polytriphenylamine triazine compound as fluorescent probes for use in the detection of TNT content in water and the detection of drug salbutamol sulfate solution.

[0025] The present invention first synthesizes a triphenylamine-triazine monomer, and then successfully prepares two polymers by CO coupling reaction. The structure and stability of the polymer are characterized by infrared, nuclear magnetic resonance, thermal analysis and other means, and its photophysical parameters such as ultraviolet absorption spectrum, fluorescence spectrum, fluorescence lifetime and quantum yield are tested. The DA type polytriphenylamine triazine compound has a high responsiveness to the drug salbutamol sulfate solution and can be used for drug quality detection; in addition, it has a strong luminescence performance in water and can be well used for the detection of trace TNT. The DA type polytriphenylamine triazine compound has a fluorescence quenching response to the salbutamol sulfate solution, and the detection limit of TNT is 39 to 70nM. At the same time, it shows good anti-interference ability and is almost not affected by potential factors such as pH, other nitro compounds, metal cations and anions.

[0026] The beneficial effects of the present invention are as follows:

[0027] The DA type polytriphenylamine triazine compound provided by the present invention is responsive to drug detection such as salbutamol sulfate solution, and has the advantages of low detection limit and good detection stability in the detection of explosives such as TNT in water. The existing detection methods are not as good as the compounds in the present invention, and the preparation method thereof is simple and has a high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 (a) Infrared spectrum (A: 4-hydroxybenzamidine hydrochloride; B: 4-diphenylaminobenzaldehyde; C: TPATz-2OH); (b) H-NMR spectrum of TPATz-2OH.

[0029] Figure 2 (a) IR spectra of PTPATzS and PTPATzK; (b) H-NMR spectrum of PTPATzS; (c) H-NMR spectrum of PTPATzK.

[0030] Figure 3 TGA (a) and DSC (b) of the polymer.

[0031] Figure 4 (a) UV-visible absorption spectrum and fluorescence spectrum of polymer powder; (b) transient fluorescence decay curve of polymer powder.

[0032] Figure 5 (a) UV-visible absorption spectrum of PTPATzS; (b) UV-visible absorption spectrum of PTPATzK; (c) fluorescence spectrum of PTPATzS; (d) fluorescence spectrum of PTPATzK.

[0033] Figure 6 Linear fit between the Stokes shift (Δν) of PTPATzS (a) and PTPATzK (b) and the orientation polarizability (Δf) of the solvent.

[0034] Figure 7 Fluorescence spectra of PTPATzS (a) and PTPATzK (c) in different ratios of THF / H2O; Change curves of fluorescence intensity and maximum emission wavelength of PTPATzS (b) and PTPATzK (d) in different ratios of THF / H2O.

[0035] Figure 8 (a) Detection of TNT by PTPATzS; (b) Stern-Volmer equation fitting curve of PTPATzS; (c) Detection of TNT by PTPATzK; (d) Stern-Volmer equation fitting curve of PTPATzK.

[0036] Fig. 9The response time curves of PTPATzS and PTPATzK to TNT.

[0037] Fig.10 (a) The detection of TNT by PTPATzS is affected by pH value; (b) The detection of TNT by PTPATzK is affected by pH value.

[0038] Fig.11 Fluorescence spectra of PTPATzS (a) and PTPATzK (c) solutions after adding different nitro compounds; Fluorescence intensity changes of PTPATzS (b) and PTPATzK (d) solutions after adding different nitro compounds.

[0039] Fig.12 Fluorescence spectra of PTPATzS (a) and PTPATzK (c) solutions after adding different metal ions; Fluorescence intensity changes of PTPATzS (b) and PTPATzK (d) solutions after adding different metal ions.

[0040] Fig.13 Fluorescence spectra of PTPATzS (a) and PTPATzK (c) solutions after adding different anions; Fluorescence intensity changes of PTPATzS (b) and PTPATzK (d) solutions after adding different anions.

[0041] Fig.14 The average particle size and fluorescence intensity changes of aqueous solutions of PTPATzS (a) and PTPATzK (b) within 21 days. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.

[0043] Example 1

[0044] 1. Experimental instruments and raw materials

[0045] Table 1 Experimental drugs

[0046]

[0047]

[0048] Note: AR is analytical grade and SP is grade 4 grade.

[0049] Table 2 Main experimental equipment

[0050]

[0051] 2. Preparation of polymers

[0052] 1. Synthesis of monomers

[0053] As shown in reaction formula (I), a compound of triphenylamine-triazine structure is synthesized. The specific preparation method is as follows: 4-hydroxybenzamidine hydrochloride (3.80 g, 22 mmol), 4-diphenylaminobenzaldehyde (2.73 g, 10 mmol) and cesium carbonate (8.14 g, 25 mmol) are placed in a three-necked bottle equipped with a stirrer. Subsequently, 20 mL of dimethyl sulfoxide solution is added dropwise to the bottle, stirred for half an hour to fully mix and dissolve the reactants, and then reacted at 120°C for 18 hours. After the reaction is completed, the obtained reaction solution is poured into water to promote the precipitation of the product, and then filtered and washed with distilled water for multiple times. After washing, ethyl acetate is used for multiple full extractions, and then anhydrous sodium sulfate is added to the extract for drying to remove the water in the solvent. The filtrate is collected by suction filtration, and the solvent is removed by reduced pressure distillation to obtain a crude product. The crude product was purified by column chromatography (developing solvent: ethyl acetate: petroleum ether = 1:2 mixed solvent, Rf value 0.3) and recrystallized using methanol. Finally, after 5 hours of vacuum drying, 2.69 g of yellow-green crystalline product was obtained, recorded as TPATz-2OH, with a yield of 53%.

[0054]

[0055] 2. Synthesis of polymers

[0056] As shown in reaction formula (II), two polytriphenylamine-triazine fluorescent materials were synthesized by CO coupling, which were recorded as PTPATzS and PTPATzK. Taking the preparation of PTPATzS as an example, 4,4'-difluorodiphenyl sulfone (2.54g, 10mmol), TPATz-2OH (5.08g, 10mmol) and anhydrous potassium carbonate (2.07g, 15mmol) were placed in a three-necked bottle equipped with a stirrer under a nitrogen atmosphere, and then 10mL of cyclopentane sulfone and 5mL of chlorobenzene solution were added dropwise, stirred to mix the reaction system evenly, and the reaction was continued at 160℃ for 8 hours. After the reaction was completed, the reaction solution was poured into anhydrous ethanol for precipitation, washed with distilled water several times, extracted with anhydrous ethanol at 80℃ for 12 hours through a Soxhlet extractor, and vacuum dried for 5 hours to obtain 6.29g of yellow powder polymer with a yield of 87%.

[0057]

[0058] 3. Polymer Characterization and Performance Testing Methods

[0059] (1) Thermal stability

[0060] The DSC and TGA curves of the polymers were obtained by differential scanning calorimeter Netzsch DSC214 and thermal analyzer Mettler TGA2, respectively, in a nitrogen atmosphere at a heating rate of 10 K / min.

[0061] (2) Fluorescence properties in different solvents

[0062] 1 mg of polymer was added into a glass bottle containing 20 mL of different solvents (cyclohexane (HEX), chloroform (TCM), ethyl acetate (EA), dichloromethane (DCM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethanol (EtOH), methanol (MeOH)). After complete dissolution, the polymer was excited with 365 nm ultraviolet light to test the fluorescence spectrum of the polymer in each solvent.

[0063] (3) Fluorescence quantum yield

[0064] Prepare a polymer solution with an absorbance of less than 0.05 at a UV wavelength of 360 nm, and use quinine sulfate solution ( The solvent is 0.05 mol / L H2SO4 aqueous solution) as a reference sample. After using a fluorescence spectrometer to test the fluorescence spectrum of the polymer in this solvent, the quantum yield is calculated using formula (1-1):

[0065]

[0066] In the formula, st and x represent the standard sample and the sample to be tested respectively. is the fluorescence quantum yield, F is the integrated area of ​​the fluorescence peak, f is the absorption factor, and n is the refractive index of the solvent.

[0067] (4) Fluorescence lifetime

[0068] The fluorescence decay curve of the polymer was measured using a transient fluorescence spectrometer, and the fluorescence lifetimes τ1 and τ2 were obtained by second-order exponential fitting. Then, the average fluorescence lifetime (<τ> avg ).

[0069]

[0070] Where τ1 and τ2 are the fluorescence lifetimes obtained by second-order exponential fitting; B1 and B2 are the proportions of the fluorescence lifetime τ1 and τ2, respectively; <τ> avg represents the average fluorescence lifetime.

[0071] (5) Fluorescence properties of polymers in H2O / THF dual solvent system

[0072] Prepare 10 mL of H2O / THF solutions with a ratio of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10 (v / v) respectively, and add 100 μL of a 1 g / L polymer solution to each solution in turn. After oscillation and mixing, test the fluorescence spectra of the polymers at different water contents under 365 nm ultraviolet excitation.

[0073] (6) Detection of polymers on drug salbutamol sulfate solution and TNT

[0074] 1) Detection of TNT by polymers PTPATzS and PTPATzK

[0075] Prepare 500mL of 0.01g / L polymer solution (THF / water = 1:9, v / v), take 10mL and add it to a glass bottle, then add 0μL, 0.25μL, 0.5μL, 0.75μL, 1μL, 1.5μL, 2μL, 2.5μL, 3μL, 4μL and 5μL of 1g / L TNT solution respectively. After equilibrium, test the fluorescence spectrum under 365nm ultraviolet light excitation. The Stern-Volmer constant (K) of the polymer for TNT is calculated by fitting equations (1-3) and (1-4). SV ) and limit of detection (LOD).

[0076]

[0077]

[0078] Where I0 is the initial fluorescence intensity of the fluorescent probe before adding TNT, I is the fluorescence intensity after the addition of TNT, [Q] is the concentration of TNT in the sample being tested, and K is sv is the Stern-Volmer constant, C L is the detection limit of the fluorescent probe, and S is 15 times the standard deviation of the blank sample.

[0079] 2) Detection of the drug salbutamol sulfate solution by polymer

[0080] A certain weight of the polymer was weighed and transferred into a commercially available salbutamol sulfate solution, and the fluorescence spectrum was tested under 365 nm ultraviolet light excitation.

[0081] (7) Response speed of polymer to TNT

[0082] Prepare 10 mL of a solution (H2O / THF=9:1, v / v) and add it to a glass bottle, then add 10 μL, 20 μL, 40 μL, 60 μL, 80 μL, and 100 μL of a 5 g / L polymer solution respectively, then measure 3.5 mL of each and add them to a cuvette, and also add 70 μL of a 2 mM TNT solution to the cuvette, and test under 365 nm ultraviolet light excitation to obtain a curve of the fluorescence intensity of the solution changing with time.

[0083] (8) Effect of pH on polymer properties

[0084] Prepare 10mL of solution with a pH value in the range of 1-12 and a volume ratio of H2O and THF of 9:1. Then, add 100μL of 1g / L polymer THF solution to each solution. After mixing evenly, add 3.5mL to the cuvette and test the fluorescence spectrum of the polymer solution under 365nm ultraviolet light excitation. Subsequently, add 70μL of 2mM TNT solution to the previous cuvette. After the two fully respond, test the fluorescence spectrum of the polymer and TNT combined under 365nm ultraviolet light excitation.

[0085] (9) Polymer selectivity for TNT

[0086] First, prepare a 10 mM concentration of metal ion nitrate (Ag + 、Al 3+ , Ca 2+ 、Co 3+ , Cu 2+ , Fe 2+ , Fe 3+ Mg 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ ) and nitro compound (o-chloronitrobenzene (CNB), o-nitrophenol (NP), 1,3-dinitrobenzene (DNB), m-nitrobenzene (NT), nitrobenzene (NB), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (DNT), octogen (HMX), hexogen (RDX)) solution. Then, prepare 500mL of 0.01g / L polymer solution (THF / water = 1:9). Take 10mL of polymer solution and put it into a glass bottle, and then add 20μL of the prepared metal ion or nitro compound solution to each sample. After the fluorescence is stable, use 365nm ultraviolet light to excite and test its fluorescence spectrum.

[0087] (10) Stability of polymer solution

[0088] 200 mL of 0.01 g / L polymer solution (THF / H2O=1:9) was prepared, and 20 mL of the solution was taken out every three days for particle size analysis and fluorescence spectrum measurement for 21 days.

[0089] 4. Results and Discussion

[0090] 1. Characterization of Monomers

[0091] The structure of TPATz-2OH was characterized by IR and H-NMR. Figure 1 (a) is the infrared spectrum of 4-hydroxybenzamidine hydrochloride, 4-diphenylaminobenzaldehyde and TPATz-2OH. It can be seen that before and after the reaction, the -1 The broad peak at 1688 cm -1 The characteristic peak of C=O stretching vibration of 4-diphenylaminobenzaldehyde disappears at 815cm -1 The characteristic peaks of triazine CH bending vibration and 3400cm -1 The appearance of the hydroxyl stretching vibration peaks proves the successful preparation of TPATz-2OH. Figure 1 (b) The hydrogen atom peak positions of TPATz-2OH in the range of 6.5-9 ppm correspond to its structure, which also confirms the successful synthesis of TPATz-2OH.

[0092] 2. Characterization of polymers

[0093] Both PTPATzS and PTPATzK are yellow powdery solids, and their structures are characterized by IR and NMR. Figure 2 (a) is the infrared spectrum of the polymer. In the PTPATzS spectrum, 1296 and 1146 cm -1 The characteristic peaks of asymmetric stretching vibration and symmetric stretching vibration of sulfone group appear at 815cm -1 The characteristic peak of triazine out-of-plane bending vibration appears at 1650cm -1 The characteristic peak of carbonyl stretching vibration appears, 815cm -1 The characteristic peak of triazine out-of-plane bending vibration appears at the 40°. The H NMR spectra of PTPATzS and PTPATzK are shown in Figure 2 As shown in (b) and (c), in the range of 6-9ppm, the hydrogen atom peak position corresponds to the polymer molecular structure one by one. At the same time, the hydroxyl NMR peak of PTPATzS and PTPATzK at 10.5ppm has disappeared, which means that the hydroxyl group of TPATz-2OH has been completely reacted during the reaction. The IR and NMR characterization results confirmed the successful preparation of the polymer.

[0094] 3. Study on thermal stability of polymers

[0095] Figure 3 The TGA and DSC curves of the polymers are shown in the figure. As can be seen from the figure, polytriphenylamine-triazine has excellent thermal stability. In a nitrogen atmosphere, there is almost no weight loss below 500°C. The temperatures of 5% weight loss are 564°C and 538°C, respectively, and the residual carbon rates are 57% and 50% when heated to 800°C. Their excellent thermal stability is attributed to the strong polarity of the triazine group, which makes the polymer structure very rigid. In addition, the polymer prepared by CO coupling has a higher molecular weight, which can improve the thermal stability of the polymer. The DSC test results show that the glass transition temperatures of PTPATazS and PTPATzK are 220°C and 197°C, respectively. The reason for the large difference in glass transition temperature may be that the polarity of the sulfone group is higher than that of the carbonyl group, making PTPATzS more rigid; at the same time, the sulfone group, as a strong polar group, has a higher intermolecular effect than the carbonyl group, such as the dipole-dipole effect formed by the sulfone group-sulfone group. These factors will make the polymer with sulfone group have a higher glass transition temperature.

[0096] 4. Study on the photophysical properties of polymers

[0097] Both PTPATzS and PTPATzK have triphenylamine-triazine structures. This DA-type structure promotes the generation of ICT effect, and the twisted structure of the main chain can effectively inhibit the fluorescence quenching phenomenon in the aggregated state, which is a prerequisite for its ability to detect TNT in water. Its photophysical properties were characterized. Figure 4 The UV-visible absorption spectra, fluorescence spectra and fluorescence decay curves of PTPATzS and PTPATzK powders are shown. Because the structures of the two are highly similar, the powders of PTPATzS and PTPATzK show similar UV absorption in the range of 200-500nm. Under ultraviolet light, PTPTzS exhibits strong green fluorescence, while PTPATzK exhibits strong blue-green fluorescence. Through fluorescence spectrum testing, the maximum emission wavelengths of PTPATzS and PTPATzK are 509nm and 499nm, respectively. The difference is attributed to the different effects of diphenyl sulfone and benzophenone structures on the electronic distribution of triazine. It is worth noting that the small molecule TPATz-2OH, which also has a triphenylamine-triazine structure, shows almost no fluorescence properties in the solid, while PTPATzS and PTPATzK show high-intensity fluorescence emission in the solid state, which also confirms the feasibility of the idea of ​​inhibiting the stacking of molecules in the solid by twisting the polymer main chain.

[0098] like Figure 4(b) As shown in Table 3, both PTPATzS and PTPATzK have long fluorescence lifetimes. The two fluorescence lifetimes τ1 and τ2 of PTPATzS are 1.9ns and 4.9ns, respectively. The two transition modes account for 43.57% and 56.43%, respectively. The average fluorescence lifetime <τ>avg is calculated to be 3.62ns. The two fluorescence lifetimes τ1 and τ2 of PTPATzK are 2.4ns and 5.2ns, respectively. The two transition modes account for 50.37% and 49.63%, respectively. The average lifetime <τ>avg is calculated to be 3.75ns. PTPATzS and PTPATzK have a higher fluorescence lifetime τ2 ratio and a larger average fluorescence lifetime <τ>avg. A longer fluorescence lifetime usually represents a higher radiation transition ratio, which is the reason for its high quantum yield (powder state, PTPATzS: PTPATzK: ).

[0099] Table 3 Quantum yield and fluorescence lifetime of polymer powders

[0100]

[0101] Note: In the table is the absolute quantum yield measured by the fluorescence spectrometer through an integrating sphere; τ1 and τ2 are the fluorescence lifetimes of the second-order exponential fitting; <τ>avg is the average fluorescence lifetime.

[0102] like Figure 5 As shown in Figure 4, the UV-visible absorption and fluorescence spectra of the polymers in n-hexane (HEX), chloroform (TCM), ethyl acetate (EA), dichloromethane (DCM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethanol (EtOH) and methanol (MeOH) were tested, and their photophysical parameters are summarized in Table 4. PTPATzS and PTPATzK both have two absorption peaks in the range of 300-500nm, and their two absorption peaks have wavelengths around 300nm and 390nm, which are the π-π* transition of the benzene ring in the polymer and the ICT absorption of the triphenylamine-triazine structure, respectively. In solvents of different polarities, both PTPATzS and PTPATzK show a small amount of solvent color change. For example, the wavelengths of the two absorption peaks of PTPATzS in a low-polarity solvent (HEX) are 304nm and 403nm, respectively; while in a high-polarity solvent (DMF), the wavelengths are 295nm and 391nm, respectively. In solvents of different polarities, the wavelengths of these two absorption peaks shift by up to 9nm and 12nm.

[0103] Table 4 Photophysical properties of PTPATzS and PTPATzK in different solvents

[0104]

[0105] Note: Δf in the table is the orientation polarizability of the solvent; λabs is the maximum absorption wavelength in the polymer solution; is the maximum emission wavelength in the polymer solution; Δν is the Stokes shift of the polymer solution; is the fluorescence quantum yield of the polymer solution.

[0106] In addition, PTPATzS and PTPATzK show significant differences in emission wavelengths in solvents of different polarities. In low-polarity solvents (HEX), the maximum emission wavelength of PTPATzS is 483nm, while in high-polarity solvents (DMF), its value is 552nm, and there is a 69nm maximum emission wavelength shift between the two. PTPATzK shows a stronger solvent color change effect, with a maximum emission wavelength of 471nm in low-polarity solvents (HEX) and 548nm in high-polarity solvents (DMF), and there is a 74nm emission wavelength shift between the two. This is due to the presence of triphenylamine-triazine in the structure of PTPATzS and PTPATzK, which can achieve charge transfer (CT) from electron donors to electron acceptors in the excited state. The CT process will significantly increase the dipole moment of the excited state, and high-polarity solvents have a more significant effect on the stability of excited states with higher dipole moments, which can reduce the excited state energy to a certain extent, causing the emission wavelength to redshift.

[0107] It is worth noting that the quantum yields in different solvents show that the quantum yields of the two polymers in high polarity solvents are significantly lower than those in medium and low polarity solvents. This is due to the stronger solute-solvent interaction in high polarity solvents, which dissipates the excited state energy through non-radiative transitions and weakens the fluorescence emission of the polymer. The physical parameter of orientation polarizability (Δf) is introduced to describe the polarity of the solvent, and the Lippert-Mataga equation is used to further study the color change behavior caused by solvent polarity. Figure 6 As shown in the figure, by linearly fitting the Δf of different solvents with the Stokes shift (Δν) of the polymer in the corresponding solvent, the results show that the linear relationship between Δν and Δf is poorly fitted, but the overall trend is that the greater the polarity of the solvent, the greater the Stokes shift. These results indicate that the excited states of PTPATzS and PTPATzK in different solvents may exist in both local excited (LE) states and intramolecular charge transfer (ICT) states. Generally, the fluorescence emission in low-polarity solvents is mainly attributed to the LE state, while in high-polarity solvents, the polymer is more likely to form a stable distorted conformation, which promotes charge separation and significantly increases the component of the ICT state.

[0108] The luminescence properties of PTPATzS and PTPATzK in dilute solution and aggregated state were studied in a binary solvent system (tetrahydrofuran / water). Figure 7 As shown, PTPATzS and PTPATzK show similar trends in different water contents. In the water content range of 0-10%, as the water content increases, the fluorescence of the polymer decreases significantly, while the maximum emission wavelength redshifts significantly. This is because when a trace amount of water is added to the tetrahydrofuran solution, the polarity of the solution becomes higher, which induces the molecule to enter a twisted intramolecular charge transfer (TICT) state, which is a special ICT effect. When the two planar DA structures of the molecule are connected by a single bond, the electrons enter the TICT state after being excited. In this state, the excited state molecules usually return to the ground state by non-radiative transitions such as single bond rotation. In the water content range of 10%-60%, as the water content increases, polymer nanoparticles in the solution gradually form, and the polymer changes from solution luminescence to aggregate luminescence. Since the twisted structure of the polymer main chain can effectively inhibit the mutual stacking of polymer chains, the fluorescence of the polymer gradually increases in this water content range. When the water content is in the range of 60%-99%, as the water content increases, the polymer particles in the solution aggregate to a greater extent, causing their fluorescence to gradually decrease. The quantum yield of the aggregates of PTPATzS and PTPATzK in water was tested. It can still reach 0.35 and 0.57.

[0109] 5. Detection of TNT by polymer

[0110] The concentration of TNT in the solution was gradually increased, and the change in the fluorescence intensity of the polymer solution was tested and analyzed using the Stern-Volmer equation. Figure 8 As shown in (a) and (c), the fluorescence intensity of the polymer solution gradually weakened with increasing TNT concentration in the solution. When the TNT concentration was 0.22 μM, the fluorescence intensity of the PTPATzS solution was quenched by 12%; when the TNT concentration was 2.2 μM, the fluorescence intensity of the solution was quenched by 83%. The detection effect of PTPATzK on TNT was slightly inferior to that of PTPATzS. When the TNT concentration was 0.44 μM, the fluorescence intensity of the PTPATzK solution was quenched by 14%; when the TNT concentration was 8.8 μM, the fluorescence intensity was quenched by 78%. The curve was fitted by the Stern-Volmer equation ( Figure 8As can be seen in (b) and (d), when the TNT concentration is lower than 1.1 μM, there is a strong linear correlation between the ratio of the initial fluorescence intensity of PTPATzS to the fluorescence intensity after quenching equilibrium (I0 / I) and the concentration of TNT (cTNT). When the TNT concentration is higher than 1.1 μM, the relationship between I0 / I and cTNT gradually deviates from linearity. Similarly, PTPATzK has a good linear relationship when the TNT concentration is lower than 8.8 μM, but gradually deviates from linearity when the concentration is higher than 8.8 μM. The Stern-Volmer constants (KSV) of PTPATzS and PTPATzK calculated by the Stern-Volmer equation are as high as 6.97×10 5 M -1 and 3.88×10 5 M -1 The detection limits (LOD) were as low as 39 nM and 70 nM, which exceeded the performance of most reported TNT fluorescent probes (Table 5). Fig. 9 As shown, TNT, PTPATzS and PTPATzK added to the polymer solution all exhibited ultrafast response speeds, and could complete the response to TNT within 15 s without continuous oscillation.

[0111] Table 5 Performance comparison of PTPAS and reported TNT detectors

[0112]

[0113] [1]Xu YW,Zhong C,Zhang BY,et al.Facile preparation oftetraphenylethylene-based porous polymer with dual role of adsorption and detection for trinitrotoluene[J].Polymer,2023,288:126454.

[0114] [2]Mukherjee A,Bhattacharya S,Chakravarty M.An unprecedentedpyridine-based dinuclear mixed-valent ReI / VII oxo-bridged complex:asolvatochromic and AIE-active probe for nanomolar detection of picric acidand trinitrotoluene[J].Dalton Transactions,2021,50(26):9144-9157.

[0115] [3]Liao Y,Hu L,Huang J,et al.A facile and novel AIE vesicle asnanoprobe for simple and rapid detection of TNT in water[J].SpectrochimicaActa Part A:Molecular and Biomolecular Spectroscopy,2024,307:123617.

[0116] [4]Dong W,Fei T,Scherf U.Conjugated polymers containingtetraphenylethylene in the backbones and side-chains for highly sensitive TNTdetection[J].RSC Advances,2018,8(11):5760-5767.

[0117] [5]Dong W,Ma Z,Chen P,et al.Carbazole and tetraphenylethylene basedAIE-active conjugated polymer for highly sensitive TNT detection[J].MaterialsLetters,2019,236:480-482.

[0118] [6] Komikawa T, Tanaka M, Tamang A, et al. Peptide-functionalized quantumdots for rapid label-free sensing of 2,4,6-trinitrotoluene[J]. BioconjugateChemistry, 2020, 31(5): 1400-1407.

[0119] [7] SK.Pyrene substituted amphiphilic ROMP polymers asnano-sized fluorescence sensorsfordetectionofTNTinwater[J].Polymer,2019,183:121868.

[0120] [8]Doan BK, Tran TVT, Nguyen TH, et al. One-pot synthesis of star-shapedconjugated oligomers based on 3-hexylthiophene, pyrene and triphenylamine as TNT chemosensors[J]. Journal of Photochemistry and Photobiology A: Chemistry, 2020, 394: 112496.

[0121] In addition, PTPATzS and PTPATzK have good fluorescence quenching properties for salbutamol sulfate solution.

[0122] 6. Effect of pH on polymer properties

[0123] The effects of pH on the fluorescence and detection properties of PTPATzS and PTPATzK solutions were studied. Fig.10 (a) shows that PTPATzS exhibits a small fluorescence change in the pH range of 2-8, while the fluorescence intensity is severely weakened at pH <2 and pH>8. Fortunately, even though the fluorescence performance of PTPATzS is affected by strong acid and strong alkalinity, the detection process of TNT is not affected. PTPATzK also exhibits a similar phenomenon ( Fig.10 (b)), in the pH range of 3-9, the fluorescence is less affected by pH, while at pH < 2 and pH > 9, the fluorescence performance is greatly affected by pH. Similarly, the detection process is not affected by pH.

[0124] PTPATzS and PTPATzK are highly sensitive to acidity and alkalinity, which may be due to the increase in the polarity of the solvent under strong acid and alkaline conditions. Both PTPATzS and PTPATzK have a strong TICT effect. After the polarity is enhanced, the side triphenylamine can dissipate energy in the excited state by rotating the single bond in a non-radiative transition, resulting in a decrease in fluorescence intensity. The detection of TNT is almost unaffected by acidity and alkalinity, which may be due to the fact that the triphenylamine structure is sufficiently stable under acidic and alkaline conditions, and the electron-deficient characteristics of TNT are more inclined to interact with the triphenylamine group of the electron-rich structure. This quenching channel is not affected under acidic or alkaline conditions. In addition, the fluorescence is not completely quenched after adding TNT under pH = 12, which may be due to the formation of J-aggregates by TNT under alkaline conditions. The formation of this dimer will increase the steric hindrance effect when interacting with triphenylamine, and at the same time, this process will also reduce the concentration of TNT in the solution.

[0125] 7. Study on the selectivity of polymers for TNT

[0126] Different nitro compounds (CNB, DNB, DNT, HMX, NB, NP, NT, RDX), metal ions (Ag + 、Al 3+ , Ca 2+ 、Co 3+ , Cu 2+ , Fe 2+ , Fe 3+ Mg 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ ) and anions (F - , Cl - Br - ,I - , SO4 2- 、SO3 2- 、CO3 2- PO4 3- 、HPO4 2- ,AcO - 、NO3 - ) and other potential interfering substances that may affect the fluorescence of the polymer to investigate the selectivity of the material for TNT. Fig.11 , Fig.12 and Fig.13 As shown, the fluorescence of PTPATzS and PTPATzK was little affected by common nitro compounds, metal ions and anions, but showed a significant quenching response to TNT.

[0127] 8. Study on the stability of polymer solution

[0128] The changes in particle size and fluorescence properties of the polymer solution were continuously observed over 21 days to provide a simple assessment of its stability and shelf life. Fig.14 As shown, after standing for 21 days, the fluorescence intensity and average particle size of the polymer solution did not change much, which indicates that it has a long shelf life.

[0129] 9. Conclusion

[0130] First, a triphenylamine-triazine monomer TPATz-2OH was successfully synthesized, which exhibits high-intensity fluorescence in solution, but almost no fluorescence properties in the aggregated state. Based on this monomer, two polymers PTPATzS and PTPATzK were successfully prepared by CO coupling reaction. The twisted structure of the polymer main chain makes them in solution (chloroform, PTPATzS: PTPATzK: ) and solid (PTPATzS: PTPATzK, ) state. PTPATzS and PTPATzK not only have good fluorescence quenching properties for salbutamol sulfate solution, but also show high sensitivity to TNT, with the Stern-Volmer constant (KSV) reaching 6.97×10 5 M -1 and 3.88×10 5 M -1 , the detection limit (LOD) is as low as 39nM and 70nM. At the same time, PTPATzS and PTPATzK can complete the response to TNT within 15s. In addition, PTPATzS and PTPATzK have good anti-interference ability for the detection of salbutamol sulfate solution and TNT.

Claims

1. A triphenylamine-triazine structure compound, characterized in that: The structural formula of the triphenylamine-triazine structure compound is shown in the following formula <Ⅰ>:

2. The method for preparing the triphenylamine-triazine structure compound according to claim 1, characterized in that: The method comprises the steps of dropping dimethyl sulfoxide into a mixture containing 4-hydroxybenzamidine hydrochloride, 4-diphenylaminobenzaldehyde and cesium carbonate, heating the mixture for a period of time, precipitating a product and subjecting the product to multiple extractions to obtain a crude product, and purifying the crude product by column chromatography.

3. The preparation method according to claim 2, characterized in that: The molar ratio of 4-hydroxybenzamidine hydrochloride, 4-diphenylaminobenzaldehyde and cesium carbonate is 2-2.5:1-1.2:2-2.5; preferably, the reaction temperature is 120-140° C., and the reaction time is 16-20 hours.

4. The preparation method according to claim 2, characterized in that: The column chromatography uses ethyl acetate and petroleum ether as developing solvents, and the volume ratio thereof is 1:

2.

5. A DA type polytriphenylamine triazine compound, characterized in that: The structural formula of the DA type polytriphenylamine triazine compound is shown in the following formula <Ⅱ>: Wherein, X is -SO2- or -CO-.

6. The DA type polytriphenylamine triazine compound according to claim 5, characterized in that: The average lifetime <τ>avg of the DA type polytriphenylamine triazine compound is 3.62 to 3.75 ns, and the fluorescence quantum yield in water is is 0.39-0.53; preferably, the thermal decomposition temperature of the DA type polytriphenylamine triazine compound is 538-564°C, and the glass transition temperature is 197-220°C.

7. The DA type polytriphenylamine triazine compound according to claim 5, characterized in that: The DA type polytriphenylamine triazine compound has a fluorescence quenching response to a drug salbutamol sulfate solution, and a detection limit of TNT in water is 39-70 nM.

8. The method for preparing the DA type polytriphenylamine triazine compound according to any one of claims 5 to 7, characterized in that: It is prepared in a nitrogen atmosphere by a one-step CO coupling reaction using 4,4'-difluorodiphenyl sulfone, a triphenylamine-triazine structure compound and potassium carbonate.

9. The preparation method according to claim 8, characterized in that: The molar ratio of the 4,4'-difluorodiphenyl sulfone, the triphenylamine-triazine structure compound and potassium carbonate is 1-1.2:1-1.2:1.5-2.0; preferably, the reaction temperature of the CO coupling reaction is 150-180°C, and the reaction time is 6-12 hours.

10. The use of the triphenylamine-triazine structure compound according to claim 1 and the triphenylamine-triazine structure compound prepared by the method according to any one of claims 2 to 4, as well as the DA type polytriphenylamine triazine compound according to any one of claims 5 to 7 and the DA type polytriphenylamine triazine compound prepared by the method according to any one of claims 8 to 9 as fluorescent probes for detecting TNT content in water and detecting the drug salbutamol sulfate solution.

Citation Information

Patent Citations

  • S-triazine derivatives and application thereof to organic electroluminescence devices

    CN103539751A

  • Biphenyl-substituted triazines as light stabilizer

    CN1178527A